Denmark : Financial Sector Assessment Program-Technical Note-Insurance Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2020)
Denmark's insurance sector is highly developed with a particularly high penetration and density in the life sector. Traditionally, work-related life insurance and pension savings are offered as a combined package, and life insurance companies dominate the market for mandatory pension schemes for employees. The high penetration explains the overall size of the insurance sector, which exceeds those of peers from other Nordic countries and various other EU member states. Assets managed by the insurance industry amounted to 146 percent of the GDP at end-2018, compared to 72 percent for the EU average.